(3ZGjI GdeQGO aj TQc fcJ GdEQTGOs - (3GdYGedj, TeS GdOjf, GdTgjO GdChd, GdTgjO GdChd, eMeO Hf ecj Hf eMeO, J (B786(3g` (B1384(3es ((3eMeO MSjf Hf ceGd GdOjf GdfMhjs)
(3ChdgG (B:s
(3ChdgG(B: (3Gddg CMeO Ydi ShGHZ GdCfYGe hJQGOa GdCbSGe (B... (3cJGH GdWgGQI, GdcJGH dZI aYGd ef GdcJH hgh GdLeY haj cJHJ GdbQf EPG LeYgGs
(3BNQgG (B:s
(3BNQgG(B: (3aj ebOe GdQCS aChVMg hNQL GdQeM ef eDNQg agj hGMOI aj XGgQ aJGhi YdeGFfG QMege Gddg(B. (3hMjK GfJgJ GdeSGFd GdJj JYdb GdZQV HHMKgG hGdhSGFd (B... (3hGdMeO ddg GdPj ef YdjfG HGdESdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 109s
(3GdPQjYI, L (B16: 14s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis